A review of biopolymer-based wood consolidants for archaeological wood preservation - Crosby, Jack (2023)
Biopolymers have been considered as a source of potential consolidating or film-forming agents for many years, with the Oseberg artefacts attracting the interest approaches based upon cellulose, chitosan and other biopolymers. With a strong a strong platform now established in using our understanding of these polymers there is now interest in seeing what modifications can be made to the polymer chain, whether this be the methylation or the addition of hydroxypropyl groups, and what changes these may have on the consolidation of severely degraded and waterlogged archaeological wood samples. This review focuses on four separate polymers of interest, namely hydroxymethylcellulose, hydroxypropylcellulose, hydroxypropylchitosan and sporopollenin. Cellulose and Chitosan based consolidants have a strong basis as consolidants and have been applied in the past to the Oseberg and Mary Rose restoration projects. Sporopollenin, with its reputation as possibly the toughest natural polymer, is a dream consolidant that could permanently solve the Oseberg Problem but issues surrounding solvents and ligin/cellulose interactions remain a big issue.